Adoption of Occupational Safety and Health Measures in the Informal Manufacturing Sector in Kampala, Uganda (Global Journal of Science Frontier Research, 2023)
Globalization has facilitated the rapid increase in informal employment and has been associated with the "generation of employment that is flexible, precarious and insecure". Many informal jobs are not only "flexible, precarious and insecure but are also hazardous and take place in unhealthy and unsafe environments. Informal sector workers operate in inhumane conditions and makeshift places without sanitary facilities. The cost in human terms of the existence of the informal sector and ways in which it is sustained is tragic. Enforcement and compliance with safety and health standards are unknown. There are high and tragic incidences of occupational related accidents and injuries that go unabated in Kampala. The purpose of the study was to assess compliance levels of occupational safety and health (OSH) measures among informal manufacturing sector workers in Kampala, Uganda. A cross sectional survey design was used, both qualitative and quantitative data were collected. Three hudred and eighty eight (388) firms were sampled among the manufacture of metal products, furniture, textiles and clothing, concrete and brick, paper and paper recycling, repair of machinery and other manufacturing sectors of the informal sector.
Keywords: adoption; compliance; occupational safety health measures; informal sector